2015
DOI: 10.1128/aac.04125-14
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Humans Study of the Safety, Tolerability, and Pharmacokinetics of ACT-451840, a New Chemical Entity with Antimalarial Activity

Abstract: Emerging resistance to antimalarial agents raises the need for new drugs. ACT-451840 is a new compound with potent activity against sensitive and resistant Plasmodium falciparum strains. This was a first-in-humans single-ascending-dose study to investigate the safety, tolerability, and pharmacokinetics of ACT-451840 across doses of 10, 50, 200, and 500 mg in healthy male subjects. In the 200-and 500-mg dose groups, the effect of food was investigated, and antimalarial activity was assessed using an ex vivo bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…ACT‐451840, a preclinical drug molecule, is another example of a compound with potent activity against sensitive and resistant P. falciparum strains (Fig. ) . Preclinical studies of CT‐451840 have been carried out by several groups in partnership with academic and industrial researchers .…”
Section: Chemical Compounds Effective Against Various Life Stagesmentioning
confidence: 99%
See 1 more Smart Citation
“…ACT‐451840, a preclinical drug molecule, is another example of a compound with potent activity against sensitive and resistant P. falciparum strains (Fig. ) . Preclinical studies of CT‐451840 have been carried out by several groups in partnership with academic and industrial researchers .…”
Section: Chemical Compounds Effective Against Various Life Stagesmentioning
confidence: 99%
“…6). [70][71][72] Preclinical studies of CT-451840 have been carried out by several groups in partnership with academic and industrial researchers. 73 This compound exhibited a range of activities against multiple life cycle stages of the human malaria parasite P. falciparum (asexual and sexual) and P. vivax (asexual).…”
Section: Pipeline Drug Candidatesmentioning
confidence: 99%
“…ACT-451840 is a potent piperazine-containing compound that targets all three stages (rings, trophozoites, and schizonts) of P. falciparum asexual blood stage development. Phase I clinical trials with this compound, developed by Actelion Pharmaceuticals with support from the Medicines for Malaria Venture, documented a good safety and tolerability profile with no serious adverse events (Bruderer et al, 2015). Heterologous expression studies found that ACT-213615, a previous analog in this chemical series, bound to the P. falciparum transporter PfMDR1 (multidrug resistance-1), which is a parasite ortholog of the mammalian dug efflux transporter P-glycoprotein 1.…”
Section: Introductionmentioning
confidence: 99%
“…ACT-451840( 132)i sacandidate for preclinical and clinical development. [21] Further resultswill be reported in due course.…”
Section: Discussionmentioning
confidence: 87%
“…The compounds act through a novel and unknown mechanism of action. ACT‐451840 ( 132 ) is a candidate for preclinical and clinical development . Further results will be reported in due course.…”
Section: Discussionmentioning
confidence: 98%